2018
DOI: 10.3389/fevo.2018.00003
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of the Anthroposphere since 50,000 Years: An Ecological Replacement of Megaherbivores by Humans in Terrestrial Ecosystems?

Abstract: Megaherbivores fulfilled a number of important ecological functions in terrestrial ecosystems and behaved as ecological engineers since 300 million years until around 12,000 years ago. These essential ecological functions include opening vegetation cover, selective seed dispersal and nutrient recycling and spreading. Thanks to these effects, megaherbivores change the vegetation structure where they live, with cascading effects on smaller herbivores and also on climate. The late Pleistocene extinction strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 104 publications
1
27
0
Order By: Relevance
“…The effect of the absence of large predators may have been compensated by humans' over-exploitation on large herbivores (Darimont et al 2015), thereby substituting the role of large carnivores in the ecosystem -although often this effect has been, and still is, far beyond, leading to strong population reductions or losses of the herbivore species (Ripple et al 2015, Doughty et al 2016a, Malhi et al 2016. At the same time, humans may to some extent have replaced the ecological functioning of megaherbivores through agricultural practices (Bocherens 2018), albeit again the effect of humans has overcompensated these processes with detrimental effects (Ellis et al 2013, Ellis 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the absence of large predators may have been compensated by humans' over-exploitation on large herbivores (Darimont et al 2015), thereby substituting the role of large carnivores in the ecosystem -although often this effect has been, and still is, far beyond, leading to strong population reductions or losses of the herbivore species (Ripple et al 2015, Doughty et al 2016a, Malhi et al 2016. At the same time, humans may to some extent have replaced the ecological functioning of megaherbivores through agricultural practices (Bocherens 2018), albeit again the effect of humans has overcompensated these processes with detrimental effects (Ellis et al 2013, Ellis 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, one could use active anthropogenic management, in some cases (Owen‐Smith, 1989). Conservationists already apply various manual conservation interventions and these techniques (e.g., coppicing) may emulate some effects of extinct megafauna (Bocherens, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another circumstance, seen as positive by conservationists, is when introduced animals replace lost native seed dispersers (Vizentin‐Bugoni et al , 2019). It has even been suggested that humans partly replaced the role of extinct megaherbivores in dispersing certain species (Bocherens, 2018).…”
Section: Hmd Effects On Vegetation Dynamicsmentioning
confidence: 99%